Dynamic anomaly detection using cross layer security in MANET. (April 2017) - Usha, G.; Rajesh Babu, M.; Kumar, S. Saravana
Abstract: Mobile ad hoc networks (MANETs) are one of the emerging technologies of wireless communication, in which each node in the MANET acts as a router. In an ad hoc network, any node can communicate with any other node in the network. However, this infrastructure of mobile nodes makes this system more vulnerable to various types of attacks. A black hole attack is one such attack in which the packet is dropped maliciously. In this paper, we propose a security solution known as the honeypot-based dynamic anomaly detection using cross-layer security (HBDADCS). The proposed technique detects and isolates black hole attacks from the ad hoc network. In this work, various novel algorithms are used which involve honeypot methodology. These technologies are proposed in order to detect and isolate black hole attacks from the network. Simulation-based results prove that the proposed technique has better packet delivery and end to end to delay with a decreased network load solely due to control packets compared to the other existing techniques.